The human methyltransferase ZCCHC4 catalyses N6-methyladenosine modification of 28S ribosomal RNA. Issue 2 (4th December 2019) - Pinto, Rita; Vågbø, Cathrine B; Jakobsson, Magnus E; Kim, Yeji; Baltissen, Marijke P; O'Donohue, Marie-Françoise; Guzmán, Ulises H; Małecki, Jędrzej M; Wu, Jie; Kirpekar, Finn; Olsen, Jesper V; Gleizes, Pierre-Emmanuel; et al.
Abstract: RNA methylations are essential both for RNA structure and function, and are introduced by a number of distinct methyltransferases (MTases). In recent years, N 6 -methyladenosine (m 6 A) modification of eukaryotic mRNA has been subject to intense studies, and it has been demonstrated that m 6 A is a reversible modification that regulates several aspects of mRNA function. However, m 6 A is also found in other RNAs, such as mammalian 18S and 28S ribosomal RNAs (rRNAs), but the responsible MTases have remained elusive. 28S rRNA carries a single m 6 A modification, found at position A4220 (alternatively referred to as A4190) within a stem–loop structure, and here we show that the MTase ZCCHC4 is the enzyme responsible for introducing this modification. Accordingly, we found that ZCCHC4 localises to nucleoli, the site of ribosome assembly, and that proteins involved in RNA metabolism are overrepresented in the ZCCHC4 interactome. Interestingly, the absence of m 6 A4220 perturbs codon-specific translation dynamics and shifts gene expression at the translational level. In summary, we establish ZCCHC4 as the enzyme responsible for m 6 A modification of human 28S rRNA, and demonstrate its functional significance in mRNA translation.